How central is the middle?: Middle class discourses and social policy design in Germany - Barbehön, Marlon; Haus, Michael (Creating target publics for welfare policies, 2018)
When it comes to assessing the status of the welfare state or the necessity of political reforms, in many countries the middle class serves as a major point of reference. In such debates, the middle class and the welfare state typically constitute an ambivalent relationship as the middle class is both financing and benefiting from the systems of social security. The middle class is therefore a particularly important target group to secure the functioning of social policies and the long-term stability of welfare institutions. At the same time, however, the socio-structural boundaries, the interests and the normative meaning of “the middle class” are not objectively given but find their way into political discourses and decisions through specific ways of perception and interpretation. As regards the design of social policies, “the middle class” can therefore be expected to serve as a major landmark for political orientation while at the same time it is open to a variety of meanings. Starting from here, the chapter investigates for the case of Germany how, firstly, “the middle class” becomes a meaningful discursive category in public debates and, secondly, how these discourses leave their marks in the design of social policies. By building on newspaper articles, we aim at identifying the discursive practices of constructing “the middle class” which then function as a major yardstick in political processes, both as an explicit target of welfare policies and as an implicit point of reference for negotiating “appropriate” policy designs.
Gesehen am 20.01.2022